INOVASI SOSIAL MASYARAKAT DALAM PENDEKATAN ASSET BASED COMMUNITY DEVELOPMENT DI KAMPUNG SAWAH DESA PEMATANG JOHAR KECAMATAN LABUHAN DELI, KABUPATEN DELI SERDANG - Sally Marisa Sihombing; Jefri Pernando Hutagalung (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2023)
Innovation is a must for local governments, including village governments. Law No. 83 of 2017 concerning the establishment of general guidelines for village innovation programs is used to explore the potential of resources by utilizing the capital owned by the community. This study aims to answer how social innovation is in the development of rice field tourism villages and what assets or capital contribute to the development of rice field tourism villages in Pematang Johar Village. The method used is a descriptive method with a qualitative approach. Data collection techniques were carried out by interview, observation and documentation. The results showed that the development of rice field tourism villages has social innovation criteria, namely overcoming social problems, creating new institutional relationships or collaborations, increasing community capacity, improving community welfare and having a sustainable or long-term effect. The capital that contributes is natural capital that contributes to the object of attraction in the form of a very wide expanse of rice fields, cultural capital that is still preserved and displayed to attract the attention of tourist visitors, social capital shown in interaction and a sense of belonging, capital for building contributes to accessibility and political capital contributes to the institutional component.